STUDI ISLAM MELAYU: Melacak Karya-karya Kyai H. Anwar Seribandung-Palembang - Hafidhuddin Hafidhuddin (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2016)
South Sumatra, socially intellectual, is one area that has a tradition of writing that is strong enough. Many found religious books or other themes that are found in this area. The abundance of these writings can not be released to the role of the scholars who actively and creatively to formulate the teachings of Islam to the people. This tradition is experiencing dynamic development along with the development of his time. The tradition of writing in South Sumatra typical "Arabic-Malay", can be traced historically in Palembang Sultanate era, which is the palace-centric. When the Sultanet Palembang by the Government of the Netherlands East Indies, this tradition pesantran move to boarding schools. One of the schools that is Pesantren Seribandung with the main characters K.H. Anwar bin Kumpul. From the hands of this phenomenal born clerics many religious books that can be enjoyed until now. Keywords: -Malay Islam, -Kyai Anwar, -Pesantren Seribandung.